DIVERSIFIKASI PANGAN SEBAGAI SALAH SATU STRATEGI PENINGKATAN GIZI BERKUALITAS DI KOTA PROBOLINGGO (STUDI KASUS DI KECAMATAN KANIGARAN) - SUKESI, KEPPI; SHINTA, AGUSTINA (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2011)
The objective of the research is to identify the Nutrition Adequacy Rate in Probolinggo and the strategies to increase the quality of balanced nutrition. Aside of measuring the food intake, the quality of nutrition in the daily menu is also measured by observing the balance between food groups in the menu. This balancecan be observed from the contribution of each of the food groups in producing macro elements of nutrition. The information on the component of food being consumed is obtained through people’s “recall one-day consumption” interview approach.